The Lipo-Body Lift: Operative Technique. Issue 2 (February 2019) - Bertheuil, Nicolas; Chaput, Benoit; Bergeat, Damien; Morvan, Christophe; Mocquard, Camille; Watier, Eric
Abstract : Summary: Bariatric surgery induces massive weight loss, which results in global and complex skin deformities. Lower body lift procedure has become the gold standard for lower trunk reconstruction. The authors describe in this video the lipo-body lift technique in detail. The video is divided into 4 parts: part 1, indications and preoperative markings; part 2, posterior contouring; part 3, anterior contouring; and part 4, preoperative and postoperative results. Patient selection and technical key points of the technique are discussed. The lipo-body lift method is an important component of reconstructive strategies and should be widely offered to patients who experienced massive weight loss.